2016
DOI: 10.1021/acs.jpcc.6b00269
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Oxide Layer in Radiation-Induced Corrosion of Copper in Anoxic Water

Abstract: The influence of a pregrown copper oxide layer on radiation-induced corrosion of polished copper in pure anoxic water has been explored. The resulting amount of copper oxide formed during corrosion was measured with cathodic reduction, and the concentration of dissolved copper in solution was measured with inductively coupled plasma atomic emission spectroscopy. The identity of corrosion products and their topography was determined with Raman spectroscopy and scanning electron microscopy, respectively. Nonirra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…For instance, it was found that Fe-reducing bacteria can substantially enhance corrosion rates by destabilizing magnetite at temperatures below 100°C (Schütz et al, 2015;Spark et al, 2017). Mixed cation/anion solutions, like most natural waters, might also lead to a different outcome with respect to corrosion and particularly to film formation (Lee et al, 2006).In NWD, γ radiation originating from the spent nuclear fuel may produce powerful oxidants by radiolysis (HO•cm) aq, H2O2) that enhance metal corrosion substantially (Björkbacka et al, 2016).…”
Section: Implications For Geotechnical Applicationsmentioning
confidence: 99%
“…For instance, it was found that Fe-reducing bacteria can substantially enhance corrosion rates by destabilizing magnetite at temperatures below 100°C (Schütz et al, 2015;Spark et al, 2017). Mixed cation/anion solutions, like most natural waters, might also lead to a different outcome with respect to corrosion and particularly to film formation (Lee et al, 2006).In NWD, γ radiation originating from the spent nuclear fuel may produce powerful oxidants by radiolysis (HO•cm) aq, H2O2) that enhance metal corrosion substantially (Björkbacka et al, 2016).…”
Section: Implications For Geotechnical Applicationsmentioning
confidence: 99%
“…The peaks at 525 cm −1 , 625 cm −1 , 147 cm −1 , and the faint peak at 220 cm −1 indicate the presence of Cu 2 O. [20][21][22][23][36][37][38][39] The detection of this phase in the absence of any discrete deposited crystals suggests Cu 2 O is present as a pervasive surface film. Given the roughness of the corroded surface, it is possible these Raman responses are surface-enhanced 29 and that the variations in peak intensities reflect the different corrosion rates on different crystal faces, with strong signals surface enhanced.…”
Section: Resultsmentioning
confidence: 99%
“…At higher dose rates (80 Gy/h to 770 Gy/h), more extensive corrosion was observed with the deposited corrosion product film (predominantly Cu 2 O) thought to play a significant role in amplifying the influence of ϒ-radiation. 23 Under unsaturated aerated conditions more relevant to these studies, modest dose rates (100 Gy/h [90°C to 150°C]) 24 also lead to the formation of an apparently protective Cu 2 O layer, the corrosion rate being only marginally greater (∼1.5 times) than that in the absence of radiation. At a higher dose rate (700 Gy/h), cupric nitrate (Cu 2 NO 3 (OH) 3 ) was formed, again suggesting the establishment of oxidizing surface redox conditions sufficient to cause oxidative breakdown of the Cu 2 O base layer and the incorporation of radiolytically-generated NO − 3 into the corrosion product.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Copper is material believed as corrosion resistant in wet bentonite environment of radioactive waste deep geological repositories. It is candidate material for outer case in Scandinavian concept [1][2][3][4][5] and for coating in Canadian [6][7][8][9][10]. Copper is also one of the candidate materials for construction of canisters in Czech concept [11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%